The association of childhood maltreatment with Internet addiction: the serial mediating effects of cognitive emotion regulation strategies and depression. (June 2023) - Guo, Yuan-Yuan; Gu, Jing-Jing; Gaskin, James; Yin, Xue-Qin; Zhang, Yu-Han; Wang, Jin-Liang
Abstract: Objectives: Childhood maltreatment, cognitive emotion regulation strategies (CERSs), and depression can be important in adolescents' Internet addiction. The current study aims to investigate the direct effect of childhood maltreatment on Internet addiction and its indirect effects via CERSs and depression. Participants and setting: 4091 adolescents (age M = 13.64, SD = 1.59; 48.9 % males) were recruited from a public school in China. Methods: In a cross-sectional design, participants completed the Childhood Trauma Questionnaire-Short Form (CTQ-SF), the Cognitive Emotion Regulation Questionnaire-Short version (CERQ-Short), the Self-Rating Depression Scale (SDS), and the Internet Addiction Test (IAT). A latent structural equation model was used to test the hypotheses. Results: After controlling for age, childhood maltreatment was directly associated with adolescents' Internet addiction ( β = 0.12, p < 0.001). Meanwhile, the serial mediating effect via maladaptive CERSs and depression was 0.02 (95 % CI [0.01, 0.04]), and via adaptive CERSs and depression was 0.001 (95 % CI [0.0004, 0.002]), demonstrating significant serial mediating role of CERSs and depression in this relationship. No gender difference was observed. Conclusions: The findings suggest that maladaptive CERSs and depression can be potential mechanisms relating childhood maltreatment to adolescents' Internet addiction, while adaptive CERSs can be a less influential factor for reducing Internet addiction.